The Christmas menorahs : how a town fought hate - Cohn, Janice; Farnsworth, Bill (Morton Grove, Ill. : A. Whitman, 1995)
Describes how people in Billings, Montana, joined together to fight a series of hate crimes against a Jewish family.
Elem. School Library Collection.
School Library Journal.
Publisher's Weekly.
4.5
3-6
Keywords: Jews -- Montana -- Billings -- Juvenile literature; Antisemitism -- Montana -- Billings -- Juvenile literature; Hate crimes -- Montana -- Billings -- Juvenile literature; Hanukkah -- Juvenile literature; Jews; Prejudices; Antisemitism; Hate crimes; Hanukkah; Jews -- Billings (Mont.); Prejudices; Antisemitism; Hate crimes; Hanukkah; Jews; Antisemitism; Hate crimes; Hanukkah; Prejudices; Billings (Mont.) -- Ethnic relations -- Juvenile literature; Billings (Mont.); Billings (Mont.) -- Ethnic relations; Montana